Carcinogenic and nephrotoxic alkaloids aristolochic acids upon activation by NADPH : cytochrome P450 reductase form adducts found in DNA of patients with Chinese herbs nephropathy - Stiborová, M; Hájek, M; Frei, E; Schmeiser, H H (General physiology and biophysics, 2001)
Aristolochic acid (AA), a naturally occurring nephrotoxin and carcinogen, has been found to be implicated in an unique type of renal fibrosis, designated Chinese herbs nephropathy (CHN), and associated with the development of urothelial cancer in CHN patients. Understanding, which enzymes are involved in AA activation and/or detoxication is important in the assessment of individual susceptibility of humans to this natural carcinogen. Using the nuclease P1 version of the 32P-postlabeling assay we examined the ability of microsomal NADPH: CYP reductase to activate AA to metabolites forming DNA adducts. Renal and hepatic microsomes, containing NADPH:CYP reductase, generated AA-DNA adduct patterns reproducing those found in renal tissues in patients suffering from a renal fibrosis CHN and urothelial cancer. 7-(Deoxyadenosin-N6-yl)aristolactam I, 7-(deoxyguanosin-N2-yl)aristolactam I and 7-(deoxyadenosin-N6-yl)aristolactam II were identified as AA-DNA adducts formed by AAI. Two AA-DNA adducts, 7-(deoxyguanosin-N2-yl) aristolactam II and 7- (deoxyadenosin-N6-yl) aristolactam II, were generated from AAII. According to the structures of the DNA adducts identified, nitroreduction is the crucial pathway in the metabolic activation of AA. The identity of NADPH: CYP reductase as activating enzyme in microsomes has been proved with different cofactors and an enzyme inhibitor. Alpha-lipoic acid, a selective inhibitor of NADPH: CYP reductase, significantly decreased the amount of the adducts formed by microsomes. Likewise, only a cofactor of the enzyme, NADPH, supported the DNA adduct formation of AAI and AAII, while NADH was ineffective. These results demonstrate an involvement of NADPH: CYP reductase in the activation pathway of AAI and AAII in the microsomal system. Moreover, using the purified enzyme, the participation of this enzyme in the formation of AA-DNA adducts was confirmed. The results presented here are the first report demonstrating a reductive activation of natural nitroaromatic compounds, AA, by NADPH: CYP reductase.
Keywords: Microsomes, Liver; Cattle; adukty DNA; Male; Enzyme Activation; Rats, Wistar; Drugs, Chinese Herbal; Models, Chemical; skot; vztah mezi dávkou a účinkem léčiva; Kidney; mužské pohlaví; potkani Wistar; Aristolochic Acids; krysa rodu Rattus; Time Factors; Phenanthrenes; kyseliny aristolochové; Animals; léky rostlinné čínské; játra; Carcinogens; NADPH-Ferrihemoprotein Reductase; karcinogeny; ledviny; zvířata; DNA Adducts; Rats; časové faktory; DNA; aktivace enzymů; NADPH-cytochrom c-reduktasa; Liver; chemické modely; Dose-Response Relationship, Drug; jaterní mikrozomy; fenantreny